Pengaruh Profitabilitas, Likuiditas, Solvabilitas, dan Aktivitas terhadap Nilai Perusahaan Makanan dan Minuman yang Terdaftar di BEI - Novita, Vika Arum; Edastami, Mayangsari (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study was conducted with the aim of investigating the impact of Profitability, Liquidity, Solvency, and Activities on Firm Value within the food and beverage sector. The analysis utilized data collected over the period from 2019 to 2022. A total of 68 data samples were analyzed from 17 companies, which were chosen through purposive sampling criteria during the research period. Secondary data were employed in this study, consisting of financial reports accessed from www.ojk.go.id and the corporate website. Utilizing the SPSS software, the study implemented logistic regression complemented by classical assumption tests and multiple regression models. It was discovered that Profitability substantially enhances Firm Value. In contrast, a marked negative correlation between both Liquidity and Solvency with Firm Value was established. Furthermore, it was determined that Activities exert no influence on the value of the firm.